Validation of the subjective vitality scale and study of the vitality of elderly people according to their physical activity - Couto, Nuno (2017)
The main aim of the study was to validate the Portuguese version of the Subjective Vitality Scale - SVS for the Portuguese elderly population through of confirmatory factorial analysis. The existence of differences in the perception of subjective vitality among sufficiently active and insufficiently active older adults was also analyzed. A total of 309 Portuguese elderly (242 females, 67 males) aged 60-90 years (M = 68.59, SD = 6.60) participated in this study. Of the total sample, 256 are sufficiently active, while 53 are insufficiently active. The results show that the model was adjusted to data in a satisfactory way (χ² = 28.95; df = 9; CFI = .97; TLI = .94; SRMR = .04; RMSEA = .08; RMSEA 90% CI = .05 - .12), and show a concurrent validity with the Portuguese version of the Satisfaction with Life Scale. The data obtained allow us concluding that the Portuguese version of the Subjective Vitality Scale can be used as a measure of subjective vitality in the Portuguese elderly population. It was also verified that the subjective perception of vitality is greater among individuals sufficiently active compared with their peers that do not reach the amount of practice of recommended physical activity.